The role of basement membrane in colorectal cancer invasion and liver metastasis - Hida, J; Matsuda, T; Kitaoka, M; Machidera, N; Kubo, R; Yasutomi, M (Cancer, 1994)
Basement membrane (BM) is a specialized extracellular matrix component that plays a key role in tumor invasion and metastasis. Immunohistochemical staining for two major components of BM, type IV collagen (C IV), and laminin (LN), utilizing avidin-biotin-peroxidase complex detection to examine 182 primary colorectal cancers (pT2 or greater) and 20 liver metastases. The distribution of C IV was the same as of LN in colorectal cancer tissue, and in normal tissue. Both C IV and LN staining were more frequently positive in the superficial zone but infrequently in the deep zone of the primary tumor. BM preservation, C IV and LN staining in both the superficial and deep zones, was seen in 18.7% of the subjects. The rate of BM preservation significantly decreased with increasing histologic grade (P < 0.01). No correlation was observed between pT number and BM preservation. The rate of BM preservation in cases of liver metastasis was 84.4%, significantly higher than the rate in cases without liver metastasis (P < 0.001). BM was observed even at the advancing front of tumor invasion and was preserved in 95.0% of the liver metastases. BM is a functional substance that appears to accompany cancer rather than function as a structural barrier against cancer invasion and liver metastasis.